Students’ long-term orientation role in e-learning success: A Brazilian study - Cidral, W. A.; Aparicio, M.; Oliveira, T. (Heliyon, 2020)
E-learning can play an important role in the solution to educate a large quota of the population in significant countries. Studies point out that cultural characteristics can influence e-learners’ performance. Our main goal is to understand the e-learning success drivers in Brazil. Our research proposes a model that analyzes students' long-term orientation role in the Brazilian e-learning context. We collected 297 answers from a survey of higher education students in nine regions. Data were analyzed through a quantitative method. Results indicate that information and collaboration quality, and e-learner satisfaction explain e-learning systems usage. Our model indicates that students' long-term orientation influences the positive relationship between e-learning systems' use and the perceived net benefits. We also found that system and information quality, and e-learning systems’ use are determinants of e-learning user satisfaction. Collaboration quality and information quality are determinants of e-learning systems usage. E-learning usage and user satisfaction explain overall e-learning net benefits, and long-term orientation has a moderating effect between e-learning use and net benefits.